The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.molimm.2016.11.020
|View full text |Cite
|
Sign up to set email alerts
|

AMP kinase promotes Bcl6 expression in both mouse and human T cells

Abstract: The transcription factor Bcl6 is a master regulator of follicular helper T (TFH) cells, and understanding the signaling pathway that induces Bcl6 and TFH cell differentiation is therefore critical. IL-2 produced during T cell activation inhibits Bcl6 expression but how TFH cells evade IL-2 inhibition is not completely understood. Here we show that Bcl6 is highly up-regulated in activated CD4 T cells following glucose deprivation (GD), and this pathway is insensitive to inhibition by IL-2. Similar to GD, the gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 48 publications
(78 reference statements)
0
23
0
Order By: Relevance
“…Interestingly, recent evidence suggests that cell metabolic processes may play important roles in modulating T FH development in vivo. BCL6 was shown to repress glycolysis in activated CD4 + T cells [5, 6]. Consistently, it has been demonstrated that T FH cells exhibit diminished glycolysis and mitochondrial respiration compared to T H1 cells [7].…”
Section: Introductionmentioning
confidence: 78%
“…Interestingly, recent evidence suggests that cell metabolic processes may play important roles in modulating T FH development in vivo. BCL6 was shown to repress glycolysis in activated CD4 + T cells [5, 6]. Consistently, it has been demonstrated that T FH cells exhibit diminished glycolysis and mitochondrial respiration compared to T H1 cells [7].…”
Section: Introductionmentioning
confidence: 78%
“…Total RNA was collected from freshly sorted cells using the RNeasy Plus Micro kit (QIAGEN). qPCR reactions were performed as previously reported (32).…”
Section: Methodsmentioning
confidence: 99%
“…However, it has also been shown that expression of Bcl6 represses the glycolytic gene program (38). Consistent with this, inhibition of glycolysis pathway or glucose deprivation does not block Bcl6expressing T FH cell differentiation (39). The findings reveal a controversial role of glycolysis during T FH differentiation and suggest that glycolysis might be required for early T cell activation, but optional for differentiated mature T FH cells.…”
mentioning
confidence: 58%